2021
DOI: 10.3390/cancers13071562
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Parameters with Intracranial Outcome in Non-Small Cell Lung Cancer Patients with Brain Metastases Treated with Pd-1/Pd-L1 Inhibitors as Monotherapy

Abstract: There is a paucity of biomarkers for the prediction of intracranial (IC) outcome in immune checkpoint inhibitor (ICI)-treated non-small cell lung cancer (NSCLC) patients (pts) with brain metastases (BM). We identified 280 NSCLC pts treated with ICIs at Karolinska University Hospital, Sweden, and University Hospital of Heraklion, Greece. The inclusion criteria for response assessment were brain metastases (BM) prior to ICI administration, radiological evaluation with CT or MRI for IC response assessment, PD-1/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The combination of ICI with radiotherapy for BM has a good safety tolerance, and both local control rate and overall survival of patients are improved, compared with radiotherapy alone ( 29 ). Longer progression-free survival was also achieved with the addition of radiotherapy to ICIs ( 30 , 31 ). Due to the research period of this study, immunotherapy has not been widely used in the Chinese population, and only a few patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of ICI with radiotherapy for BM has a good safety tolerance, and both local control rate and overall survival of patients are improved, compared with radiotherapy alone ( 29 ). Longer progression-free survival was also achieved with the addition of radiotherapy to ICIs ( 30 , 31 ). Due to the research period of this study, immunotherapy has not been widely used in the Chinese population, and only a few patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous studies have been published focusing on the impact and timing of cranial RT in relation to anti- PD-1/PD-L1 therapy for metastatic NSCLC (8,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Rounis etal. ( 19 ) focused specifically on a subgroup of patients who received PD-1/PD-L1 inhibitors as treatment for NSCLC BM and found that specific clinical parameters, such as age <70 years, prior CNS radiation, and the synchronous appearance of BM, significantly affected ICB disease control. However, it is important to point out that this study was focused on the patients who received ICB as monotherapy, as opposed to the patients included in our cohort, who received any combination of CT and ICB.…”
Section: Discussionmentioning
confidence: 99%